An exploratory cross-cultural study of community-based health literacy interventions to promote the mental well-being of disadvantaged and disabled young Africans: a multi-method approach - Sharpe, Darren; Rajabi, Mohsen; Mesa, Liliana Galicia; Hanafiah, Ainul; Obuaku-Igwe, Chinwe; Davidson, Julia; Chileshe, Katongo (Frontiers in Psychiatry, 2024)
Background: This study explores the impact of community-based health literacy interventions on the health and mental well-being of disadvantaged young Africans in Zambia, Sierra Leone, Rwanda, and South Africa. The pandemic has exacerbated mental health problems amongst children and young people, underscoring the urgent need for equitable access to mental healthcare resources. Emphasising the importance of equitable access to mental healthcare resources, the research addresses educational and income disparities in low- and middle-income countries (LMICs), particularly amongst young Africans with disabilities or vulnerabilities. Methods: The study comprised 1,624 young Africans, of whom 1,592 were surveyed, while 191 later participated in in-depth interviews and focus groups. Additionally, 32 participants exclusively joined focus groups. Participants were recruited to complete the Short Warwick-Edinburgh Mental Well-being Scale (SWEMWBS), WHO-5 Well-being Index, Pandemic Anxiety Scale (PAS), and Self-rating of Happiness, as well as semi-structured interviews or focus groups. Results: The findings highlight the significance of tailored health literacy interventions in addressing mental health challenges and promoting well-being in marginalized African communities. In the sample, 43.1% (686) reported to have at least a physical disability or serious health condition and 51.4% (818) had special educational needs (SENs). Mental health scores were significantly lower in participants with two or more physical disabilities and pre-existing mental health problems. Factors significantly associated with poor mental health included poor health literacy, physical disabilities, and pre-existing mental health problems. Four main themes were generated from the thematic analysis: early childhood trajectories and mental illness experiences; positionality, open communication, and mental illness experience; mental illness experience, emotional honesty, and social stratification; and spirituality, cultural beliefs, and mental illness experience. Conclusion: The study emphasizes the need for context-specific, culturally appropriate health literacy interventions to support the mental health and well-being of young Africans in LMICs. By focusing on the lived experiences of disadvantaged groups, the research contributes to a better understanding of effective strategies for promoting health literacy and addressing health inequalities in African communities during and after health emergencies.